Use of anticoagulants increases risk of bleeding after colorectal endoscopic submucosal dissection - Yamashita, Ken; Oka, Shiro; Tanaka, Shinji; Boda, Kazuki; Hirano, Daiki; Sumimoto, Kyoku; Mizumoto, Takeshi; Ninomiya, Yuki; Tamaru, Yuzuru; Shigita, Kenjiro; Hayashi, Nana; Sanomura, Yoji; Chayama, Kazuaki (Endoscopy International Open, 2018)
Background and study aims Japanese guidelines for gastroenterological endoscopy have recommended temporary withdrawal of anticoagulants (warfarin, direct oral anticoagulants [DOAC], or heparin) to prevent hemorrhagic complications during endoscopic submucosal dissection (ESD) for colorectal neoplasias (CRNs). However, serious thrombosis might occur during temporary withdrawal of anticoagulants. The current study aimed to evaluate outcomes with anticoagulants in patients undergoing ESD for CRNs. Patients and methods This study was a single-institution retrospective cohort study based on clinical records. We assessed 650 consecutive patients with 698 CRNs who underwent ESD at Hiroshima University Hospital between December 2010 and June 2016. The patients were divided into three groups: the warfarin group (19 patients with 19 CRNs), DOAC group (7 patients with 9 CRNs), and no-antithrombotics group (624 patients with 670 CRNs). We replaced warfarin with heparin 3 to 5 days before endoscopy. Although DOAC was suspended on the morning of endoscopy, we did not replace heparin.Results Bleeding after the procedure occurred in 26.3 % (5/19), 22.0 % (2/9), and 2.7 % (18/670) of patients in the warfarin, DOAC, and no-antithrombotics groups, respectively. In the warfarin group, four patients who bled after the procedure took not only warfarin but also other antiplatelets. En bloc resection rates were 94.7 % (18/19), 100 % (9/9), and 96.6 % (647/670) in the warfarin, DOAC, and no-antithrombotics groups, respectively. No patients experienced ischemic events in the perioperative period. Conclusions Among patients undergoing ESD for CRNs, risk of bleeding was higher among patients who took anticoagulants than among those who did not. In particular, careful attention to patients who took antiplatelets in addition to warfarin before ESD for CRNs is warranted.